2021
DOI: 10.1002/jbm.b.34910
|View full text |Cite
|
Sign up to set email alerts
|

Nano/micro implant debris affect osteogenesis by chondrocytes: Comparison between ceramic and UHMWPE from hip walking simulator

Abstract: A new generation of ceramic on ceramic (BIOLOX ®delta) bearings has emerged more than 10 years ago proving a high resistance to wear and good clinical results. However, biological reactions to wear debris, particularly the nanoparticles, need to be evaluated. The first originality of this study is to start from real wear particles obtained by the hip walking simulator (CERsim). These particles were compared with particles obtained by usual methods to assess the biocompatibility of materials: press machine (CER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…1,2 However, cases of prosthesis failure due to in vivo loosening after THA are common, 3 and current studies suggest that wear particles from the relative motion of the femoral head to the acetabulum are the main cause of loosening failure. [4][5][6] Currently, artificial acetabulums are usually made of ultra-high molecular weight polyethylene (UHMWPE) materials, but with the continuous development of materials in recent years, highly cross-linked polyethylene (XLPE) has been produced and put into clinical application in order to improve the wear resistance of UHMWPE, and at the same time, high cross-linked polyethylene doped with vitamin E (VE-XLPE) has gradually gained widespread attention in order to improve the problem of insufficient oxidation resistance of XLPE. 7,8 Taddei et al 9 compared the wear resistance of three polymers, UHMWPE, XLPE, and VE-XLPE, using a hip simulator, and found that VE-XLPE acetabulums exhibited better wear resistance properties only under long-term or more severe test conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, cases of prosthesis failure due to in vivo loosening after THA are common, 3 and current studies suggest that wear particles from the relative motion of the femoral head to the acetabulum are the main cause of loosening failure. [4][5][6] Currently, artificial acetabulums are usually made of ultra-high molecular weight polyethylene (UHMWPE) materials, but with the continuous development of materials in recent years, highly cross-linked polyethylene (XLPE) has been produced and put into clinical application in order to improve the wear resistance of UHMWPE, and at the same time, high cross-linked polyethylene doped with vitamin E (VE-XLPE) has gradually gained widespread attention in order to improve the problem of insufficient oxidation resistance of XLPE. 7,8 Taddei et al 9 compared the wear resistance of three polymers, UHMWPE, XLPE, and VE-XLPE, using a hip simulator, and found that VE-XLPE acetabulums exhibited better wear resistance properties only under long-term or more severe test conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, cases of prosthesis failure due to in vivo loosening after THA are common, 3 and current studies suggest that wear particles from the relative motion of the femoral head to the acetabulum are the main cause of loosening failure. 46…”
Section: Introductionmentioning
confidence: 99%